The Impact of Food Packaging Cues on Perceived Product Quality: A Conceptual Development (Journal of Business Management and Accounting, 2017)
Research regarding the impact of food packaging cues on product quality perception is relatively new. The role of various food packaging elements on product quality perceptions remain unclear. This study examined the characteristics of food packaging cues and their impact on product quality perceptions. This study is grounded on â€œCue utilization theoryâ€ which explains the role of environmental stimuli in the formation of perceptions regarding the product. The framework of the study has been proposed by combining comprehensive set of Brand name, Price, Country of Origin, Nutritional label, Precautionary label and Perceived product quality. The research will plug the gaps in the literature of consumer behaviour and to generalize the results in the Pakistani consumer market. There is a scarcity of empirical studies which offer wide-ranging information regarding consumer mindset specifically in Asian contexts. Hence, this study provides practitioners with a framework to make appropriate marketing strategies. This study also makes theoretical and practical contributions.